Dramatic features of the Abang Dance Performance of the Efiks of Nigeria - Amaku Ene, Offiong (International Journal of English Literature and Social Sciences (IJELS), 2019)
This paper highlights the dramatic features of Abang Cultural dance, particularly in the areas of Costumes, Dance, Songs/Music, Symbols, and Gestures. The paper also examines the objectives via a general background study, a review of related scholarship and a descriptive detail of the theoretical framework upon which the work is hinged. The ethnographic research methodology was adopted for data collection during fieldwork. The findings of this enquiry concretize the idea that the Abang indigenous performance is an enthralling theatre on the go. As a matter of fact, its artistic apparatuses and dramatic orientation deepens our understanding of Efik epistemology. The paper therefore, recommends the preservation, promotion and transmission of this cultural art through the aid of technology as well as through dance competitions, dance societies, dance troupes in schools, universities and across households. In summary, this research is an attempt to address the lacuna in the critical documentation of the Abang dance of the Efik people in Cross River State, South-South Nigeria.